Predictive Modeling Using AI for Implant Failure Based on Patient Risk Factors and CBCT Data - Diya Aldakhlallah, Usman Manzoor Warraich, Jawaria Bibi, Sehar Naeem, Umar Farooq Khan, Asrar Ahmed, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Dental implant therapy has become a widely accepted treatment for tooth replacement.However, implant failure remains a concern due to patient-related and procedural riskfactors. Advances in artificial intelligence